PENGARUH SERVICE QUALITY DAN FACILITIES TERHADAP CUSTOMER LOYALTY MELALUI CUSTOMER SATISFACTION SEBAGAI VARIABEL INTERVENING PADA ALAS VEENUZ TRAWAS - Putri Dhea Lusanti; Woro Utari; Sri Suprapti (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2026)
The background of this study is driven by a phenomenon occurring at Alas Veenuz Trawas, where issues regarding customer loyalty are presumed to be closely related to the inconsistent aspects of service quality. Consequently, the research problem formulated in this study is "Does Service Quality affect Customer Loyalty through Customer Satisfaction at Alas Veenuz Trawas?". The research data were gathered through questionnaires distributed to 150 respondents who are visitors of Alas Veenuz Trawas. The collected data were then analyzed using SEM-PLS with SmartPLS 3.0 software as the analytical tool. After conducting several research stages, the results of the study reveal that: (1) Service Quality has no significant effect on Customer Satisfaction; (2) Facilities have a significant effect on Customer Satisfaction; (3) Service Quality has a direct and significant effect on Customer Loyalty; (4) Facilities have no direct and significant effect on Customer Loyalty; (5) Customer Satisfaction has a significant effect on Customer Loyalty; (6) Service Quality has no significant effect on Customer Loyalty through Customer Satisfaction; and (7) Facilities have a significant effect on Customer Loyalty through Customer Satisfaction.